2002
DOI: 10.1128/aac.46.5.1212-1217.2002
|View full text |Cite
|
Sign up to set email alerts
|

ColE1-Like Plasmid pIP843 of Klebsiella pneumoniae Encoding Extended-Spectrum β-Lactamase CTX-M-17

Abstract: The resistance of Klebsiella pneumoniae BM4493, isolated in Ho Chi Minh City, Vietnam, to cefotaxime and aztreonam was due to production of a novel ␤-lactamase, CTX-M-17. The bla CTX-M-17 gene was borne by 7,086-bp plasmid pIP843, which was entirely sequenced and which was found to belong to the ColE1 family. The 876-bp bla CTX-M-17 gene differed from bla CTX-M-14 by 2 nucleotides, which led to the single amino acid substitution Glu2893Lys. bla CTX-M-17 was flanked upstream by an ISEcp1-like element and downst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 45 publications
1
82
1
1
Order By: Relevance
“…This observation is in good agreement with the previous publication of Bradford et al (10) reporting the location of genes encoding CTX-M-5 on small non-self-transferable plasmids. It may also explain the relatively low proportion of CTX-M-5-producing isolates compared to those bearing CTX-M-3 and Neither CTX-M-8-nor CTX-M-9-related enzymes were found in this study, although in recent years ESBLs of the latter genetic group were found in other European countries (Spain [9,11,35], France [18,36], and the United Kingdom [Alobwede et al, letter]) as well as in Asian countries (Japan [41], China [14], Taiwan [22,44], Korea [28], and Vietnam [13]) and Brazil (8).…”
Section: Resultscontrasting
confidence: 48%
See 1 more Smart Citation
“…This observation is in good agreement with the previous publication of Bradford et al (10) reporting the location of genes encoding CTX-M-5 on small non-self-transferable plasmids. It may also explain the relatively low proportion of CTX-M-5-producing isolates compared to those bearing CTX-M-3 and Neither CTX-M-8-nor CTX-M-9-related enzymes were found in this study, although in recent years ESBLs of the latter genetic group were found in other European countries (Spain [9,11,35], France [18,36], and the United Kingdom [Alobwede et al, letter]) as well as in Asian countries (Japan [41], China [14], Taiwan [22,44], Korea [28], and Vietnam [13]) and Brazil (8).…”
Section: Resultscontrasting
confidence: 48%
“…PCR has been used widely to detect bla CTX-M genes, but detection of all the known variants usually required multiple reactions with specific primers for different genes (12,14). Consensus CTX-M primers have also been described (13,36), but these primers were used for amplification of bla CTX-M genes from a limited number of isolates. Consequently, very few studies have assessed countrywide prevalence of ESBLs which belong to the distinct CTX-M clusters (N. Shibata, Y. Doi, K. Shibayama, T. Yagi, and Y. Arakawa, Abstr.…”
mentioning
confidence: 99%
“…Different elements may be involved in the mobilization of bla CTX-M genes. Studies with plasmids have confirmed the potential involvement of the insertion sequence ISEcp1 in the mobility of bla CTX-M (Cao et al, 2002). CTX-M enzymes comprise a rapidly growing family of enzymes disseminated in several parts of the world (Bonnet, 2004).…”
Section: Introductionmentioning
confidence: 91%
“…ESBL-producing strains were analyzed by PCR to detect the presence of bla CTX-M , bla SHV and bla TEM genes. PCR amplification was performed using published primer pairs (Cao et al, 2002), which are as follows: MA-1 59-SCS ATG TGC AGY ACC AGT AA-39 and MA-2 59-CCG CRA TAT GRT TGG TGG TG-39 (for bla CTX-M ), OS-5 59-TTA TCT CCC TGT TAG CCA CC-39 and OS-6 59-GAT TTG CTG ATT TCG CTC GG-39 (for bla SHV ), and C 59-TCG GGG AAA TGT GCG CG-39 and D 59-TGC TTA ATC AGT GAG GCA CC-39 (bla TEM ). PCR was carried out with the buffer supplied by the manufacturer using 1 ml each primer and 0.25 ml Taq polymerase [5 U (ml PE) 21 ] (GeneAmp Gold PCR reagent kit; Applied Biosystems).…”
Section: Introductionmentioning
confidence: 99%
“…3 The movement of transposons, such as ISEcp1B, may promote resistance to gene evolution. 14,15 The identification of a new CTX-M ESBLs gene subtype, the ISEcp1B/IS903 hybrid, which is a composite of known insertion sequences is evidence that evolution is occurring during these horizontal transfers. Similar composite transposons consisting of ISEcp1B and IS903 flanking the CTX-M-1, CTX-M-9, CTX-M-15, CTX-M-17 and CTX-M-54 genes, were reported in Europe, the Americas and Asia.…”
Section: Discussionmentioning
confidence: 99%